HUBUNGAN ANTARA KADAR EKSTRAKTIF DENGAN SIFAT WARNA PADA KAYU TERAS JATI - Ganis Lukmandaru (BRIN Publishing, 2016)
Beside for its high natural durability and resistancy of weather properties, teak (Tectona grandis) wood is also valued for its beautiful grain and colour. Theoretically, wood colour is highly affected by extractive content, particularly in the heartwood. Identification of correlation between wood colour and extractive content was determined through wood colour and extractive measurements on the outer part of heartwood zone. The wood samples were collected from two locations of Perum Perhutani forest plantations, i.e. KPH Randublatung (35 trees, age class III-IV) and KPH Purwakarta (32 trees, age class VI). Samples were cut from bottom part of the trees and then ground into powder measuring of 40-60 mesh. The wood colour properties(CIE-L*a*b, CIE-L*C*h, CIE-X*Y*Z, Munsell Colour Chart and ISO Brightness) were then measured. Solubility of the teak wood extractives were determined by extracting the powder in ethanol-benzene and hot water respectively. Results showed that the range of colour properties were L*= 40-62; a* = 3-11; b* = 19-31; C* = 20-31; h = 70-82; X= 10-25; Y= 8-23; Z=4-13; H=5-8; V =3-8; C =3-6; and W (ISO Brightness) = 4-12. Different sample location resulted in different trends of correlation between colour properties and extractive contents. No significant correlation was found between extractive solubles in hot water and colour parameters. In general, the best correlations were encountered between brightness parameters from CIE-L*a*b* or ISO with ethanolbenzene extractive contents (r=- 0.54 or 0.50, respectively).